Inertial displacement of a domain wall excited by ultra-short circularly polarized laser pulses - T. Janda (Nature Portfolio, 2017)
Domain wall motion driven by ultra-short laser pulses has potential for storage of information in magnetoelectronic devices. Here the authors demonstrate the conversion of a circularly polarized femtosecond laser light into inertial displacement of a domain wall in a ferromagnetic semiconductor.